In My Flesh : Fabricating the Bulimic Body - Hodgson, Ashley (Rhodes University, Faculty of Humanities, Department of Fine Art)
My MFA exhibition In My Flesh, explores my own personal experience of an eating disorder: bulimia nervosa, through the medium of sculpture and installation. Situated in the Fine Art Sculpture and Painting building on Rhodes University campus, this practical submission takes the form of a multi-sensory installation depicting the fleshy interior of a bulimic body. The sculptural works that make up the installation resemble enlarged bodily forms and cavities, namely the mouth; the oesophagus, the stomach; the intestines; and the flesh. These anatomical forms are made from fabric which has been melted, manipulated, and stained using food and other synthetic dyes. The arrangement of the sculptural components (parts of the body affected by bulimia) does not mirror the human body exactly, and their intentionally disordered placement creates a feeling of dis-ease and disturbance for the participant experiencing the installation. This mini-thesis, In My Flesh: Fabricating the Bulimic Body, unpacks the visual, tactile and audio elements of this practice as research submission as they relate to my interest in bodily boundaries, corporeal traces and material extensions. I look at these themes as they translate into installation, and discuss the way in which bulimia is experienced, theorised and represented. I position my work in relation to the concept of the abject as proposed by Julia Kristeva, and visually analyse artworks by Mona Hatoum, Heidi Bucher and Ernesto Neto who make use of immersive installation strategies that resonate with my own practice. This supporting document considers the three conceptual elements informing my installation: embodiment, space, and materiality. In the first chapter of this document: Embodying the Bulimic Body, I address bulimia as less open to visual interpretations than other eating disorders because of its secretive and hidden nature. I go on to frame the illness in relation to theories around bodily boundaries and abjection and argue that bulimia epitomises abjection. In Chapter Two: Architecture of the Bulimic Body I engage with the idea of architectural structures as having anatomic features. I interrogate how the body moves through space, leaving traces of itself behind. Chapter Three: Fabricating the Bulimic Body concentrates on the main medium used in In My Flesh: fabric. In my discussion of this material, I unpack its metaphoric and symbolic qualities, as well as its personal resonance with my own lived experience.
Keywords: Bulimia; Human body -- Social aspects; Human figure in art; Diseases in art; Art therapy